The Misdemeanor of Illegal Speculation in Algeria, as Stated by The Law 21/15, and Its Juridical Applications - Souiki, Horiya (Indonesian Journal of Social Science Research, 2024)
The commercial business ethics, in light of the spread of illegal speculation acts and in view of the proliferation of the phenomenon of food scarcity, particularly in connection with the Corona pandemic, has compelled the Algerian legislator to reexamine and consider again the penal text that criminalizes this act through the cancellation of the Provisions of Penal Code (Articles 172 and 173). Afterwards, he established a special law that frames that issue, and then provided a number of preventive mechanisms along with a number of protective and discouraging punishments in order to put an end to that phenomenon. The present study aims primarily to examine the judicial application of the misdemeanor of illegal speculation based on the Provisions of Law 15-21.